Theoretical modeling and experimental study of dielectric loss of the multi-push-pull mode magnetoelectric laminate composites. (15th February 2018) - Xu, Bingbing; Ma, Jiashuai; Fang, Cong; Yao, Meng; Di, Wenning; Li, Xiaobing; Luo, Haosu
Abstract: In this work, we establish a dielectric loss model for multi-push-pull mode ME laminate composites. It deduces that the total dielectric loss of the ME composites equals the linear average of the dielectric loss of piezoelectric plate and epoxy resin. But further analysis of this model has indicated that we can ignore the dielectric loss of epoxy resin. To verify this model, we use three kinds of epoxy resin with different dielectric loss to fabricate multi-push-pull mode PMNT/Metglas ME laminate composites respectively. It turns out that the different kinds of epoxy resin have little influence on the total dielectric loss, capacitance and piezoelectricity of the composites, which demonstrates that our model conforms to the practical case. Therefore, we can pay more attention to the mechanical properties of epoxy resin rather than its dielectric loss on fabricating the ME laminate composites.